Exploring Sayyid Qutb's Wasatiyyah Concept in Tafsir Fi Zhilal Al- Qur'an: Implications for Religious Moderation in Indonesia - Fauziah, Debibik Nabilatul; Zulaiha, Eni; Yunus, Badruzzaman M.; Muhyiddin, Asep (Jurnal Iman dan Spiritualitas, 2025)
The term wasaṭiyyah comes from the sentence "ummatan wasaṭan" in Surah Al-Baqarah verse 143, which reflects the character of fair and best Muslims. This concept has developed into religious moderation, emphasizing the values ​​of justice and balance. In Indonesia, the understanding of religious moderation is often debated, with pros and cons related to the meaning of wasaṭiyyah and indicators of moderation that are considered forced. Sayyid Qutb, in Tafsir Fī Ẓilāl Al-Qur'ān, provides a comprehensive interpretation of the verse. This study uses a qualitative method with a comparative analytical approach, relying on data from the Tafsir book and other secondary sources. The analysis was carried out with a hermeneutic approach to understand the context of the verse. The results of the study show six indicators of wasaṭiyyah, according to Sayyid Qutb, including aqidah, thought, law, social, place, and time. This concept is relevant to religious moderation in Indonesia, especially in national commitment.